2014
DOI: 10.1016/j.jtbi.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Optimal cooperative searching using purely repulsive interactions

Abstract: Foraging, either solitarily or collectively, is a necessary behavior for survival that is demonstrated by many organisms. Foraging can be collectively optimized by utilizing communication between the organisms. Examples of such communication range from high level strategic foraging by animal groups to rudimentary signaling among unicellular organisms. Here we systematically study the simplest form of communication via long range repulsive interactions between two diffusing Brownian searchers on a one-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…We focused here on attraction-based strategies for the fish, since in our experiments fish were attracted to areas where neighbors detected food. However, previous studies have suggested other search strategies that were based on repulsion between individuals ( Tani et al, 2014 ) or on maximizing information about the location of food ( Karpas et al, 2017 ). Although our modeling framework gave an excellent fit to the data, it is possible that foraging fish combine or alternate between strategies in different environmental conditions, based on group composition or their internal state ( Farine et al, 2014 ; Michelena et al, 2009 ; Harpaz et al, 2017 ; Kurvers et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused here on attraction-based strategies for the fish, since in our experiments fish were attracted to areas where neighbors detected food. However, previous studies have suggested other search strategies that were based on repulsion between individuals ( Tani et al, 2014 ) or on maximizing information about the location of food ( Karpas et al, 2017 ). Although our modeling framework gave an excellent fit to the data, it is possible that foraging fish combine or alternate between strategies in different environmental conditions, based on group composition or their internal state ( Farine et al, 2014 ; Michelena et al, 2009 ; Harpaz et al, 2017 ; Kurvers et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…An interaction mechanism and its influence on high-order statistics, the general aim of this paper, has therefore not been thoroughly studied yet. Only few recent studies have investigated its effect on first-passage properties within a searching context [32,34], concluding that the optimal situation where the group is benefited as a whole is a mixture of independent searching and joining other members in the search. It was shown that this conclusion is independent on the mobility pattern, either Lévy or Brownian [33].…”
Section: Introductionmentioning
confidence: 99%